دراسة قياسية الميزان المدفوعات في السودان : في الفترة من 1998م - 2017 - د. أحمد عبد الرحمن عمر الطاهر عمر (White Nile Journal for Studies and Research, 2025)
The study aimed to study the affect of forgien Trade (balance of Trade) on the balance of payements in Soudan during the period 1998 - 2017. The study hypothesized that there is an inverse (négative) Relationship Be tween exports and the balance of payements deficit, and a positive (positive) relationship between imports and the balance of payements déficit. The study reached many The most important résulte are: proof of hypothèses, model integrity from mea surement problèmes, model stability and a long-term intégrative relationship between study variables. The study recommande the necessity of increasing exports, encouraging the production sector and raising production efficiency. Key words :Balance of payments , balance of trade, (ARDL) Autoregressive distributed lag.